Perencanaan strategis, sasaran program dan standard operasional prosedur (SOP) pada peminjaman dan pengembalian bahan pustaka di Perpustakaan APMD Yogyakarta - Rohmaniyah Rohmaniyah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
Strategic planning in the APMD Library is very important to do through vision and mission. This requires a review of internal and external environment of the library using SWOT analysis. The next target and work program are directed for the next 5 years. In SOP, quality service standards that will be generated by a job can be determined beforehand. This paper is conducted by qualitative and descriptive research methods. The results of this research is consists of several factors originating from the library's internal and external environment